Pengaruh Brand Respect Terhadap Lovemark Pada Produk Smartphone Asal China - Ali Wardhana; pipiyen pipiyen (UNIVERSITAS PGRI MADIUN, 2020)
Indonesia as a country that has smartphone sales growth that continues to grow and become the main and most developed market. To become the smartphone market leader, it needs Lovemark, loyalty beyond reason. This happened to 2 smartphone brands from China, Xiaomi and Vivo. This research looks at how the lovemark on the Xiaomi and Vivo brands is built through brand respect and has an impact on positive WOM and repurchase intentions. The results of this study indicate that in the Xiaomi and Vivo brand performance, brand reputation and brand trust have a positive impact on brand respect and ultimately make impact at lovemark. In addition, this study also found that lovemark has a positive impact on positive WOM and repurchase intentions. In the future research can be applied to the brands that slowing sales